Factors Related to Sleep Duration and Night Waking in Hospitalized Infants with Cyanotic Congenital Heart Disease - Sanpawut, Porntiwa; Patoomwan , Autchareeya; Wittayasooporn, Jariya (Nursing Research and Innovation Journal, 2024)
This study aims to describe factors related to sleep duration and night waking in infants aged 6–12 months old with cyanotic congenital heart disease (CCHD) who were admitted to a pediatric cardiology ward at a tertiary hospital between December 2019 and September 2021. Data were obtained using the Demographic Data Record Form, Sleep-related Factors Questionnaires (the severity of heart failure, temperament,and caregiving activity), and the Infants’ Sleep-wake States Record Form. The record forms were assessed using video recording of the infants during 24 hours, and the data were then analyzed using descriptive statistics, the Pearson product-moment correlation coefficient, and Spearman’s rho correlation. The results revealed that most hospitalized infants with CCHD had a mean total sleep duration during the 24 hours of 770.44 minutes. The average number of night waking was 14.26 times/night. According to the correlation analysis, the severity of heart failure did not show a statistically significant correlation with sleep duration or night waking. Temperament was moderately and significantly correlated with sleep duration but not with night waking. Caregiving activities were moderately and significantly correlated with sleep duration and night waking. These results demonstrate that nurses and healthcare professionals should be aware of sleep problems in infants with cyanotic congenital heart disease and plan interventions to manage sleep disturbance to ensure good sleep quality. Keywords: Congenital heart disease in infants, Cyanotic congenital heart disease, Night waking, Sleep duration